Smart mailbox notification system with solar battery charging based on IoT / Muhamad Athir Mohd Sidek ... [et al.] - Mohd Sidek, Muhamad Athir; Samsudin, Adam; Hussin, Nor Hafizah; Mohd Said, Rahaini; Hairol Anuar, Siti Haryanti; Noor Azhuan, Nur Azura; Mohd Yusoff, Nurul Hajar (UiTM Press, 2024)
The Smart Mailbox is designed to make users more aware of the existence of crucial notifications and messages in their current mailboxes. Busy people have been known to forget to take critical letters, invoices, and documents, and have even missed key deadlines due to their neglect and forgetfulness in checking their mailboxes. This happens because citizens lack a new solution or updated technology to handle the issue. The goal of this project is to create a solar-powered smart mailbox notification system that notifies the user via their smartphone. The essential components of this project are an IR sensor, a Blynk application, and solar power. The Blynk application function is to receive notifications and count letters inside the mailbox and the IR sensor identifies mail or small deliveries. The outcome shows that the initiative met all of its goals, and users will receive notifications from Blynk apps in less than 4 seconds informing them of incoming letters or other important documents. Solar power is selected as the main power used due to low environmental impacts and reduced electrical monthly bills.